Workshop Public Speaking Melatih Siswa Terampil Bicara di Depan Umum - Idawati Idawati; Benny Handayani; Khairul Anwar; Ayudia Putri; Aprillia Ratna Angela (UIR Press, 2019)
This community service activity aims to provide OSIS students with skills in publik speaking to train OSIS students to be skilled in publik speaking at Rumbai Sports High School in Pekanbaru. The material provided in the form of